TINJAUAN YURIDIS PENDAFTARAN HAK TANGGUNGAN SECARA ELEKTRONIK DI KANTOR PERTANAHAN KOTA BEKASI - Sheane Gunadi; Sri Untari Indah Artati (Fakultas Hukum Universitas Trisakti, 2021)
The Ministry of Agrarian Affairs and Spatial Planning published the ATR / KaBPN Ministerial Regulation Number 5 of 2020 about Electronic Integrated Mortgage Services in response to the fourth industrial revolution. By using this Ministerial Regulation, the Bekasi City Land Office builds an electronic mortgage system. The registration of mortgage rights is where the distinction exists. Problem formulation: legislative restrictions on electronic mortgage registration at the Bekasi City Land Office and how to register electronic mortgage rights there. The deductive logic approach is used to draw findings in normative juridical research, which is based on both secondary and primary material. The study's findings, analysis, and conclusion show that the use of electronic Mortgage Rights at the Bekasi City Land Office divide tasks between the PPAT and the Creditor, with the PPAT only going so far as to make APHT and the Creditor handling registration tasks. The challenge is that the guarantee of land rights must be certified differently from Article 10 paragraph (3) UUHT, error system and foreign nationals who have not been coordinated as users of HT-el services.